n-CAPTURE ELEMENTAL ABUNDANCES IN ACTIVE AND NON-ACTIVE STARS - Basak, N. Yu.; Mishenina, T. V.; Soubiran, C.; Kovtyukh, V. V.; Belik, S. I. (Одеські астрономічні публікації, 2010)
Abundances of Y, Zr, La, Ce, Nd, and Sm have been obtained under LTE approximationss. The program stars were observed at high resolution, high signal to noise ratio with the ELODIE echelle spectrograph (OHP, France). Among them more than 30 stars are active stars with a fraction of BY Dra and RS CVn type stars. Comparison of the behavior of n-capture elemental abundance in active and non active stars was made.